Business students at university : are they trained to cheat? / Faizah Mohd Khalid and Siti Jeslyn Hasan - Mohd Khalid, Faizah; Hasan, Siti Jeslyn (Research Management Institute (RMI), 2009)
Over decades, we have been bombarded with an increased of corporate scandals involving allegations of unethical behaviours mostly against accounting fraud. The debacles left us to ponder whether the education system implemented at university levels and education modules have taught students to be corrupted rather than acted responsibly and ethically. This study centres on business students at one of the private higher learning institutions in Malaysia. Surprisingly, the finding indicates that majority of students has cheated throughout their period of study. The research discovers that students’ cheating behaviour is influenced by their beliefs; on what constitutes cheating and the perception that cheating has become a common behaviour among other students. In addition, gender, academic performance (i.e. grade point average) and area of specialization have also significantly influenced on academic dishonesty. The results of the study illustrate that strict monitoring and fear of being prosecuted may reduce the tendency of cheating. Seeing that this situation has reached at an alarming stage, thus, the study has recommended some guidelines to the universities for its implementation. It is believed that by enhancing academic code of conducts, incorporating ethics components in subjects taught and establishing ethical community-building among students are advantageous to inculcate a sense of responsibility towards ethical behaviour and organise rigorous campaigns to promote integrity as way of life.